Samodzielność finansowa samorządów terytorialnych w krajach Europy Środkowo-Wschodniej oraz w krajach nadbałtyckich - Markowska-Bzducha, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This work is connected with one of many aspects of evaluation of the territorial self-government financial self-dependence - the comparative analysis based on the set of six measures of financial self-dependence. The aim of the work is presentation of differentiation of the degree of the territorial self-government financial self-dependence in eleven mid -eastern European and Baltic countries - Bulgaria, Croatia, the Czech Republic, Estonia, Lithuania, Latvia, Poland, Rumania, Slovakia, Slovenia and Hungary. The presentation is based on data from two years - 1998 and 2001.The examined countries are quite differentiated in respect of the financial self-dependence of self-government. In most of the examined countries in 2001 compared to 1998 there was the decrease of the degree of the territorial self-government financial self-dependence. This was the result of slower pace of public finance decentralisation than task decentralisation. And therefore, in spite of the theories connected with decentralisation, the degree of the territorial self-government financial self- dependence decreased in eight out of eleven examined countries. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 549-556